IMPLEMENTASI ASAS IN BEZIT STELLING PADA CASH COLLATERAL SEBAGAI JAMINAN ATAS PERJANJIAN KREDIT (Studi PT. Bank Rakyat Indonesia (PERSERO) KC Bojonegoro) - Khoirunnisa Diyah Permata; Anjar Sri Ciptorukmi Nugraheni (Jurnal Privat Law, 2024)
AbstractThis Articles aims to analyze the implementation of in bezit stelling principle on cash collateral as collateral for credit agreements and the execution of cash collateral by analyze first the implementation of credit agreements. This study belongs to empirical law research that is descriptive in nature. The data was obtained from primary and secondary data. Considering the result of research and discussion Based on the results of the research and discussion, a conclusion was made regarding the implementation of in bezit stelling principle on cash collateral at BRI Bojonegoro Branch Office and execution of cash collateral, credit loans use cash collateral tied to a mortgage agreement to ensure repayment of debtor debt, There is a surrender of cash collateral as a real delivery which is the legal amount of the mortgage along with the blocking of the credit. Creditor also has preference right, namely the right to precedence in the term of debt repayment over object execution result becoming the mortgage collateral objects against other creditor. If when the debtor makes a default, then BRI Bojonegoro Branch Office execute directly (parate execution) against cash collateral. Execution may be made by withdrawal for payment of debtor debt.